Kajian ‘Urf tentang Adat Ranub Kong Haba dan Akibat Pembatalannya di Aceh (Study of 'Urf' on The Custom of Ranub Kong Haba and its Cancellation in Aceh) - Roslaili, Yuni (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2019)
Ranub kang haba is a khitbah’s official process, as a bond between bride and groom. At ranub kang haba, the family of man’s side brings betel vine (ranup) as a symbol of bonding reinforcement (khong haba). Besides betel vine, the groom’s side also brings Aceh’s traditional food (penajoh), a set of woman’s clothes and gold jewelry, which is ring (jeunamae). If a few days later the bride cancels the wedding, Jeunamae will be given back as double to the man. This article tries to explain the practice of ranub khong haba and the consequences of tradition’s cancellation to  Acehnese society. This kind of study is the combination of socio legal-historical approach. Sociological approach is used to observe the patterns of society’s interaction & behavior, both that inspiring the renewal of Islam’s law and Islamic law legislation and the comformity of conciousness (which manifest in society’s behavior). The legal or juridical approach is done by considering certain elements of Islamic law, which is ‘urf concept. Historical approach is used on consideration that history analysis can see ranub kong haba practice objectively in relation with ‘urf concepts in Islam’s contexts. This study found that ranub kong haba is a local wisdom in affirmation of khitbah procession that has a base in Islamic law. However, the custom of giving the dowry back as double  that is brought in khitbah process is an ‘urf shahih practice, which actually doesn’t have any command nor forbidden in Islam. However, the matter is seen as a good thing because it can avoid us (sadd al-zariah) from breaking our promise to others.